Long-term crop residue application maintains oil palm yield and temporal stability of production - Tao, H-H; Snaddon, JL; Slade, EM; Caliman, J-P; Widodo, RH; Suhardi,; Willis, KJ (Springer Paris, 2017)
Crop residue management is an important agricultural practice that has a high potential to improve soil health and optimize crop production. Compared to annual crops, relatively little is known about crop residue management effects on the yield and temporal stability of perennial crop production. This study focused on oil palm (Elaeis guineensis), an important tropical crop that had expanded rapidly over the past decades. We aimed to understand the effects of applying a major oil palm residue, the empty fruit bunch, on crop yield and temporal stability of production. We compared 15 years of crop yield performance from a field trial in Sumatra, Indonesia. The treatments included empty fruit bunch application of three application rates (30, 60, and 90 t ha −1  year −1 ), and a reference treatment of chemical fertilizers with no addition of empty fruit bunch. Compared to the reference treatment, the cumulative crop yield over 15 years under low, medium, and high application rates of empty fruit bunch increased by 2.4, 5.9, and 4.8%, respectively. The annual crop yield and temporal stability in production were not significantly different between treatments. Soil organic carbon was significantly higher under medium application rate of empty fruit bunch compared to that under the chemical fertilizer treatment. Soil organic carbon and relative humidity were positively associated with annual crop yield with a time lag of 2 years. This study is the first to show that both crop yield and temporal variability of oil palm production can be maintained under crop residue application, compared to chemical fertilizer treatment. Furthermore, climatic conditions had strong effects on the temporal variability of oil palm production. These findings will inform the design of optimal empty fruit bunch application schemes that enhance sustainable intensification of oil palm cultivation.